Sequence stratigraphy and coal accumulation model of the Taiyuan Formation in the Tashan Mine, Datong Basin, China - Duan Hongyue (De Gruyter, 2021)
Datong Basin is a platform uplift formed in the Cenozoic era and has a significant coal-bearing geological unit in China. Tashan Mine is located in the middle-eastern part of the Datong Basin, the coal resources of the Taiyuan Formation are abundant, and the research value is enormous. Of the coal resources, coal seams 3–5 and 8 are the main. The lack of research in sequence stratigraphy, coal-forming environment, coal-accumulating model limits the layout efficiency of working face and the exploration and development efficiency of coal measures associated resources. This study used sedimentary and sequence stratigraphy and calculated and measured field drilling data to investigate the sequence stratigraphic characteristics, paleogeographic pattern, and coal accumulation model of the Taiyuan Formation. The sequence boundary and system tract boundary were identified, and the Taiyuan Formation was divided into four third-order sequences. The paleogeographic pattern was reconstructed with the third-order sequence as a unit by applying the single-factor analysis and multifactor comprehensive mapping. Additionally, the distribution characteristics of the main coal seams were clarified, and the corresponding coal accumulation model was reconstructed. The results exhibit that the sedimentary facies transformed from carbonate platform–tidal flat–lagoon–shallow water delta facies to shallow water delta facies from SQ1 to SQ2, coal seam 8 formed in interdistributary bay microfacies and peat swamp microfacies in SQ1. Transgression further expanded in SQ3, and the sedimentary facies were still dominated by the shallow water delta facies. Coal seams 3–5 are formed in distributary channel microfacies, which consist of interdistributary bay microfacies and peat swamp microfacies. The paleogeographic pattern was still dominated by shallow water delta in SQ4, in which interdistributary depressions and peat swamp microfacies widely developed. The thickness of coal seams 3–5 is in the range of 2.40–25.90 m, in which the northwestern study area is characterized by moderate water depth and sufficient fine sediment, and the widely developed distributary bay and peat swamp deposited a thick coal seam. The thickness of coal seam 8 is in the range of 0.5–10.5 m, and the thickness is stable (mostly thicker than 6 m) controlled by the widely developed lagoon, mud flat, and peat swamp microfacies and reduction water environment.